Peran Pesantren dalam Penguatan Moderasi Beragama - Balqis Najma Negara; Maula Devina Yahya; Purnomo Purnomo (Sekolah Tinggi Ilmu Tarbiyah Madani Yogyakarta, 2025)
This study examines the role of Pondok Pesantren Edi Mancoro in strengthening religious moderation within Indonesia’s multicultural society, particularly in response to the persistence of radicalism and intolerance that threaten interfaith harmony. Using a qualitative descriptive approach, data were gathered through in-depth interviews, participatory observation, and documentation of interfaith activities. The findings reveal that the pesantren actively promotes tolerance, openness, and peaceful coexistence through four main strategies: (1) establishing partnerships with non-Muslim organizations, such as Lembaga Percik and the interfaith forum SOBAT, to conduct inclusive education and community programs; (2) organizing annual interfaith dialogues where religious leaders from diverse traditions engage directly with students (santri) to exchange perspectives and bridge misunderstandings; (3) hosting multicultural seminars and internal forums such as the Mahfud Ridwan Institute to enhance critical thinking, social awareness, and cross-cultural communication skills; and (4) maintaining openness to visits and cultural exchanges with individuals and groups from various faith backgrounds, including providing residential experiences for domestic and international guests. These initiatives create experiential learning opportunities that foster mutual respect and reduce prejudices. The study highlights how the pesantren’s inclusive practices extend beyond doctrinal instruction to shape santri as agents of peace and social cohesion. By integrating traditional Islamic learning with contemporary approaches to diversity, the institution serves as both a center of religious education and a living space for interfaith engagement. The results demonstrate that pesantren-based moderation is operationalized through concrete, recurring activities that internalize values of tawassuth (middle way), tasamuh (tolerance), and ta’adul (justice), aligning with Indonesia’s constitutional mandate for religious harmony. This research contributes to the discourse on religious moderation by presenting Pondok Pesantren Edi Mancoro as a replicable model for Islamic educational institutions in countering radicalism and fostering peaceful pluralism. It affirms that pesantren are not only guardians of religious knowledge but also dynamic actors in cultivating national unity and cross-religious solidarity. The implications suggest that strengthening religious moderation requires continuous dialogue, inclusive community engagement, and openness to intercultural exchange, all of which are effectively demonstrated in the pesantren’s daily practices.